Salvage Therapy With Low-Dose Ruxolitinib Leads to a Significant Improvement in Bronchiolitis Obliterans Syndrome in Patients With cGVHD After Allogeneic Hematopoietic Stem Cell Transplantation - Zhao, Yanmin; OuYang, Guifang; Shi, Jimin; Luo, Yi; Tan, Yamin; Yu, Jian; Fu, Huarui; Lai, Xiaoyu; Liu, Lizhen; Huang, He (Frontiers in Pharmacology, 2021)
Bronchiolitis obliterans syndrome (BOS) is a life-threatening pulmonary manifestation of chronic graft versus host disease (cGVHD) post-allogeneic hematopoietic stem cell transplantation (HSCT), without a clear standard of care. This study included 30 patients undergoing an allogeneic HSCT for a hematological malignancy and the outcomes with post-HSCT BOS treated with ruxolitinib (RUXO) as a salvage treatment were reviewed. After a median duration of RUXO therapy of 9.25 (1.5–27) months, the best overall response (BOR) rate was 66.7%: three patients (10.0%) achieved complete remission, and 17 (56.7%) achieved partial remission. The median time from initiation of RUXO to achieve the best responses was 3 months. Since initiating RUXO, predicted forced expiratory volume in 1 s (FEV1)% slightly increased after 3 months and 6 months compared with measurements before RUXO in responders. Only FEV1 mild decline before ruxolitinib with a ratio ≤15% was an independent predictor to achieve a response to RUXO. Eleven patients (36.7%) had severe pulmonary infection of ≥3 grade. Following a median follow-up of 318 days after RUXO, the 2-year incidence of nonrelapse mortality and 2-year overall survival rate after RUXO among patients with BOS was 25.1% and 62.6%, respectively. Ruxolitinib is a promising treatment option to improve the prognosis of post-HSCT BOS.